Dampak Konseling Individu dan Konseling Berpasangan terhadap Penggunaan Kontrasepsi Pascasalin: Randomized Controlled Trials (RCT) - Shintiana, Linda; Nurdiati, Detty Siti; Sumarni, Sumarni (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: The achievement of Contraceptive Prevalence Rate (CPR) is 57.9%, which indicates that the Family Planning has not run optimally one of which concerns the utilization of family planning counseling as an attempt to avoid an unplanned pregnancy. The postpartum period is a period appropriate in using contraception. Some studies suggest that the counseling given by health workers will increase the interest of potential acceptors of contraception.Objective:The objective of this research is to increase the utilization of postpartum contraception counseling.Method: This research used Randomised Controlled Trial (RCT) method to provide counseling to couples and individuals. The subject of this study were the final trimester pregnant women with Simple Random Sampling and technique then were randomized to determine the intervention and control groups. Bivariable analysis use statistical test Chi Square with CI 95 % and P value <0.05 and binomial logistic regression multivariable analysis.Result and Discussion:The proportion of postpartum contraceptive utilization in the intervention group compared with the control group was 86% the percentage difference. Variable wife age and information have a significant influence on the utilization of contraception postpartum.Conclusion:The use of counseling in pairs in pregnant women effectively increases the utilization of postpartum contraception.Â Keywords: Counseling, postpartum contraception